Exploring opportunities to facilitate serendipity in search - Rahman, M. Ataur; Wilson, Max L. (ACM, 2015)
Serendipitously discovering new information can bring many benefits. Although we can design systems to highlight serendipitous information, serendipity cannot be easily orchestrated and is thus hard to study. In this paper, we deployed a working search engine that matched search results with Facebook `Like' data, as a technology probe to examine naturally occurring serendipitous discoveries. Search logs and diary entries revealed the nature of these occasions in both leisure and work contexts. The findings support the use of the micro-serendipity model in search system design.